ANALISIS PENGENDALIAN MUTU DI BIDANG INDUSTRI MAKANAN (Studi Kasus: UMKM Mochi Kaswari Lampion Kota Sukabumi) - Ilham Budiman; Sopyan Saori; Ramdan Nurul Anwar; Fitriani Fitriani; Muhamamd Yuga Pangestu (Sekolah Tinggi Pariwisata Mataram, 2021)
This study aims to determine whether the quality control carried out by SMEs Mochi Kaswari Lampion has been optimal. This research was conducted at SMEs Mochi Kaswari Lantern Sukabumi City. The method used in this journal uses quality improvement techniques that use data verbally, namely flow charts, which are describing diagrams that show all the steps in a process and show how these steps can interact with each other. The objectives achieved in the study include: Determining the quality in improving the performance of SMEs Mochi Kaswari Lanterns.